Selection of potential fungi for production of cellulase-poor xylanase from rice straw - Zahari, Nur Idayu; Md. Shah, Umi Kalsom; Mohamed Asa’ari, Ainun Zuriyati; Mohamad, Rosfarizan (College of Natural Resources, 2015)
Recently, xylanase has attracted attention in the pulp and paper industry because of its bleach-boosting properties, which reduces chemical consumption during the bleaching process. Four fungi species, namely Penicillium oxalicum T3.3, Aspergillus niger ATCC 6275, Colletotrichum gloeosporioides, and Pycnoporus sanguineus, were studied to select which fungi can best produce cellulase-poor xylanase using rice straw as a substrate. The fungi were screened for xylanase production based on the clear zone formation on a malt extract agar (MEA) plate containing xylan. P. oxalicum T3.3 and A. niger ATCC 6275 showed greater clear zone formation on the agar plate than the other two studied fungi. These fungi were grown in a liquid medium containing rice straw as the substrate. P. oxalicum T3.3 showed the highest xylanase activity (65.89 U/mL) with lowest carboxymethyl cellulase (CMCase) (1.88 U/mL) and filter paperase (FPase) activity (0.16 U/mL) after four days of fermentation at 30 °C. P. oxalicum T3.3 produced higher xylanase activity when rice straw was used as a substrate compared to commercial xylan. Thus, cellulase-poor xylanase produced from P. oxalicum T3.3 has high potential for biobleaching application in the pulp and paper industry in terms of technical and biological performance and economical aspects.